Herpetofauna do Parque Natural Municipal de Sertão, Rio Grande do Sul, Brasil - Zanella, Noeli; Paula, Almir de; Guaragni, Samara Arsego; Machado, Leonardo de Souza (Biota Neotropica, 2013)
The northern part of the state of Rio Grande do Sul was extensively deforested in recent decades, and only isolated fragments of the original vegetation remain. The Parque Natural Municipal de Sertão comprises a remnant of Atlantic Rain Forest, one of the largest fragments in northern Rio Grande do Sul. This study examined the diversity of the herpetofauna, focusing on environmental distribution, seasonality and species richness. We used complementary methods of sampling such as pitfall traps, active search and occasional encounters. We recorded 23 species of frogs, nine snakes and one lizard. With respect to the relationship between amphibians and reptiles and the structural and abiotic factors of the environment, the edge of the fragment showed higher richness and increased dominance of amphibians and reptiles than the interior. The highest amphibian abundances were found when the minimum temperatures were higher and maximum temperatures were lower. The abundance of snakes was correlated with humidity, and species richness was influenced by humidity and monthly average temperature. Our results reinforce the importance of the conservation of forested areas to the maintenance of the species